Hannah Arendt and Norwegian Muslim children's schooling: in pursuit of democratic practices. Issue 6 (3rd June 2017) - Giæver, Katrine; Jones, Liz
ABSTRACT: The aim of this paper is to consider whether Hannah Arendt's (1996) [Arendt, H. (1958/1998 ). Vita Activa. The Human Condition . Chicago: University of Chicago] concept of 'public space' is a potentially useful and creative way of thinking about aspects of Muslim children's experiences within the context of education. Following a terror attack in 2011, when 77 people were killed, the then Norwegian prime minister stated that 'our answer to this violence is more openness and more democracy but not naivety'. Accordingly, this paper draws on data so as to put concepts drawn from Arendt to work. In so doing, we indicate possibilities for 'more openness and more democracy' where Norwegian children can have Islam as an important element within their lives in ways that avoid the charge of naivety.